Thermal decomposition reaction of 3,3,6,6-tetramethyl- 1,2,4,5-tetroxane in 2-methoxy- ethanol solution - Leiva, Laura A. C. (2009)
The thermal decomposition study of 3,3,6,6-tetramethyl-1,2,4,5-tetroxane (acetone cyclic diperoxide) was carried out in 2-methoxyethanol solution in the 130-166 °C temperature range. The overall reaction follows a first-order kinetic law up to at least 75% diperoxide conversion. The activation parameters (ΔH# = 22.5 ± 0.7 kcal⋅mol–1 and ΔS# = -25.6 ± 0.5 cal⋅mol–1⋅K–1) for the unimolecular rupture of the O–O bond in the diperoxide molecule were obtained by measuring the remnant diperoxide at different reaction times by the CG technique. Acetone was detected by GC as the major organic product of the reaction.